“Introduction to Magneto-Rheological Fluid Technology & Its Application - Jakirahamad B.Makandar; Prof. Nehatrao S.A (International Journal of Innovations in Engineering Research and Technology, 2021)
Magnetorheological (MR) fluid damper are semi active control device that have been applied a wide range of practical vibration control application. In this study, the methodology adopted to get a control structure is based on the experimental results. An Experiment has been conducted to establish the behaviourof the MR damper. In this paper, the behaviourof MR damper is studied and used in implementing vibration control. The force displacement and force?velocity response with varying current has been established for the MR damper. In this paper we investigated theoretically at fabricated Magnetorheological damper by using Magnetorheological fluid. Here MR fluid developed first by mixing of prepared nano size (fe3o4) iron particle by co precipitation method. A